Study of Sprint and Vertical Jump for Indonesian Athletes: Multi-Sectorial Testing - SUKAMTI, ENDANG RINI; SAPUTRA, JUMADIL; SUGIHARTO, SUGIHARTO (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Throughout the world, many coaches and physical education teachers do not give importance to the evaluation of the physical capacities of athletes, and poor performance. This study is carried out to determine the speed and muscle power of the athletes' lower limbs. With regard to muscle speed, all the athletes evaluated were in the middle category. In conclusion, for any sports activity, we need speed and muscle power. That is why coaches and athletes need to develop all physical qualities such as speed, muscular power, strength, agility, muscular and cardiovascular endurance to obtain high performance.RESUMEN En todo el mundo muchos entrenadores y profesores de educación física no le dan la importancia a la evaluación de las capacidades físicas de los deportistas, y el bajo rendimiento. Este estudio se realiza para determinar la velocidad y  potencia muscular de las extremidades inferiores de los atletas. En lo que respecta a la velocidad muscular, todos los deportistas evaluados se encontraban en categoría media. En conclusión, para cualquier actividad deportiva, necesitamos velocidad y potencia muscular. Es por eso que los entrenadores y atletas necesitan desarrollar todas las cualidades físicas como velocidad, potencia muscular, fuerza, agilidad, resistencia muscular y cardiovascular para obtener un alto rendimiento.